Different fishing vessel-gear combinations confirm resource-use overlap in small-scale fisheries of south coast Kenya - Samuel , Bandari; Cosmas Nzaka, Munga; Mumini , Dzoga (Multidisciplinary Journal of Technical University of Mombasa, 2025)
Fish consumption globally has increased due to the rise in human population making fisheries resources vulnerable to overexploitation. The open access fisheries in Kenya coupled with the multi-fleet, multi-gear and multi-species nature of the fisheries make its management more difficult. A closer observation into the scenario proves the existence of resource use overlap among different vessel-gear combinations. This study assessed the resource use overlap among different vessel-gear combinations for the multi-gear and multi-fleet small-scale fishery in selected fishing areas in south coast Kenya. We conducted shore-based catch assessment from January 2019 to December 2021covering both the cool south east monsoon (SEM) season and the warm north east monsoon (NEM) season at Mkunguni fish landing site in Msambweni area and Shimoni fish landing site in Shimoni area. The data was analyzed for total fish landings and species composition by vessel-gear combinations, as well as analyzed for resource-use overlap. A total weight of 52.32 tons of fish was recorded over the study period, and this was higher in the NEM season (26.52 tons) than in SEM season (25.32 tons). An overall total of 321 species in 88 fish families were sampled. Mkunguni recorded more species (n = 253) than Shimoni (n = 186) and species richness was significantly higher in Mkunguni than Shimoni (p = < 0.0001). The most effective and preferred vessel-gear combinations overall were footfisher-speargun and dhows-handline. Seasonal species diversity also indicated an overlap in resource-use where different vessel-gear combinations landed multiple species with the highest number of species  recorded by gears used in combination with canoe being handline (120 ± 8 species) and basket trap (87 ± 6 species). Fishing gears used with dhows being handlines which recorded the highest mean number of species caught (73 ± 4 species) and gillnet (58 ±5 species). The observation made in the presence of similar fish species in different vessel-gear combinations that had been used in different fishing grounds is a clear indication of resource-use overlap in the small-scale fishery.
Keywords: Small-scale fisheries, Vessel-gear combinations, Resource-overlap, South coast Kenya